Grid computing for bioinformatics and computational biology - Talbi, El-Ghazali, 1965-; Zomaya, Albert Y. (Wiley series on bioinformatics., 2008)
Provides details on modern and ongoing research on Grid applications. This book discusses bio ontology and data mining; data visualization; DNA assembly, clustering, and mapping; molecular evolution and phylogeny; gene expression and micro arrays; gene identification and annotation; and molecular modeling and simulation.